NEOGENE AND QUATERNARY CONTINENTAL BIOSTRATIGRAPHY OF GREECE BASED ON MAMMALS - Koufos, G.D. (Bulletin of the Geological Society of Greece, 2016)
Most basins of Greece were filled with thick Neogene-Quaternary continental deposits, which include a large number of mammal fossiliferous sites. The investigations of the last 40 years in the various basins of Greece led to the discovery of many new fossiliferous sites. The extensive, long time and continuous excavations in the new fossiliferous sites as well as in the previously known ones - like the classical localities of Axios Valley, Pikermi and Samos Island - provided numerous fossils enriching remarkably the Greek fossil mammal record. The systematic study of these collections provided numerous data for their biochronology. Further magnetostratigraphic, radiometric or other methods of absolute chronology provided additional chronological data for the mammal faunas and the corresponding deposits. The correlation of all these data allowed the biostratigraphic classification of the continental Neogene Quaternary deposits of Greece which is given in the biostratigraphic tables of the present article. From these tables it is clear that for some time-intervals (Late Miocene, Early Pleistocene) the data are abundant allowing a detailed biostratigraphy, but for some others (Early- Middle Miocene, Pliocene, and for some time-spans of Early Pleistocene) the data are imited or missing and cannot allow an accurate and complete biostratigraphy.